PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA KONKRET TERHADAP HASIL BELAJAR MATEMATIKA MATERI BANGUN DATAR PADA SISWA KELAS 4 SD NEGERI 1 ANTIGA - Ni Kadek Damayanti; Ni Made Andani Dwipayanti; Ni Luh Tika Sawitri; I Made Sujana Adnyana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of the Discovery Learning model assisted by concrete media on mathematics learning outcomes in plane geometry material for elementary school students. This research was motivated by the low mathematics learning outcomes of students caused by learning activities that were still teacher-centered and the limited use of learning media. This study used a quantitative approach with a quasi-experimental design involving an experimental class and a control class. The experimental class was taught using the Discovery Learning model assisted by concrete media, while the control class used conventional learning methods. Data were collected through pretest and posttest instruments and analyzed using descriptive statistics and t-test analysis. The results showed that students who learned through the Discovery Learning model assisted by concrete media achieved higher posttest scores compared to students who learned through conventional methods. The use of concrete media also increased students’ learning motivation, participation, and understanding of plane geometry concepts. Therefore, the Discovery Learning model assisted by concrete media had a positive and significant effect on students’ mathematics learning outcomes in elementary school